A holistic assessment of the invasion of signal crayfish (Pascifastacus leniusculus) in Great Britain: understanding the invasion of signal crayfish through their distribution, variations in traits across their invasion continuum and the attitudes of key stakeholders - Rodriguez Valido, Cesar (2024)
Invasive non-native species (INNS) are one the biggest threats to global biodiversity. In Great Britain (GB), signal crayfish (Pacifastacus leniusculus) is a particularly problematic INNS. As well as numerous economic, environmental, and social impacts, signal crayfish are believed to be the leading cause behind the decline of white-clawed crayfish (Austropotamobius pallipes), the only native crayfish species in GB. Whilst one of the most studied case studies of an INNS in GB, there are still many unanswered questions when it comes to its invasion. There are still important questions around the current state of signal and white-clawed crayfish in GB, the level of variability in the traits of the INNS, and the attitudes of stakeholders towards the whole situation. This thesis aimed to address these questions through three separate but related research chapters spanning these topics. In Chapter 3, we used observational data from a range of different sources, including citizen science, to map out the current and historic distribution of signal crayfish and white-clawed crayfish in GB. The chapter also used a variety of different datasets (climatic, water quality, land-use etc.) to understand the environmental tolerance of each crayfish species. For Chapter 4, we tested whether there is a difference in morphological and behavioural traits in signal crayfish between sites that they have recently (<5 years) invaded (invasion-front) and those that they have colonized for a longer (>15 years) period (invasion-core). The chapter used established assays to test for these traits in the signal crayfish that are caught in each area. Finally, for Chapter 5, we conducted semi-structured interviews and a small exercise with relevant stakeholders to compare their attitudes towards different aspects of the invasion of signal crayfish in GB. we used thematic analysis to analyse the interviews and establish the prominent themes that mattered most to the stakeholders. In Chapter 3, we see that the pattern of signal crayfish advances and white-clawed crayfish retreat is still taking place. We identify that signal crayfish are actively advancing in the areas that contain the remaining populations of white-clawed crayfish (northern England and Wales). Through the principal component analysis (PCA) of factors, we see that the environmental space that signal crayfish have been observed is narrowly wider than that for white-clawed crayfish, with generally similar patterns between the two species. In Chapter 4, we find that signal crayfish at invasion-front sites are significantly smaller than those found at invasion-core sites. As well as seeing that the location along the invasion continuum has a significant impact on some traits, we also see that the river that signal crayfish are found in influences their morphological and behavioural traits. In Chapter 5, we see that the stakeholders tended to agree on certain topics but had different attitudes on others. For example, those stakeholders in larger organisations/government bodies tended to believe that we should limit anthropogenic interactions with signal crayfish (as they believe this was a major driver of their spread), whereas those in smaller/more local organisations felt that individual organisations should have more freedom when it comes to how they manage/interact with the INNS. The findings of this thesis demonstrate that signal crayfish are a dangerous INNS that can rapidly colonize a large much of GB due to its wide environmental tolerance and variability with its population. Likewise, throughout all the chapters, it is clear the decisions made by humans have had a strong influence on this invasion. From the initial decision to introduce the species, the slow response by policymakers, those who perceive that the economic benefit of signal crayfish still outweighs the dangers it poses and transport them to new areas or the lack of political will to create effective management solutions. It may be too late to effectively manage signal crayfish to protect the white-clawed crayfish in GB, but we must learn from our mistakes so that we can effectively manage the future INNS that pose a threat.